GEJALA DEPRESI PADA REMAJA SMK SATU BANGSA HARMONI BATAM - Fitta Deskawaty; Andi Asda Astiah; Nurul Wahyudi Raharjo (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2025)
ABSTRACT Background: One Nation Harmoni School is a formal educational institution under the auspices of the New Satubangsa Harmoni Foundation. The purpose of this study is to determine The correlations between bullying behavior with depression symptomps among Vocational High School in batam. Depression is a group of symptoms with the main picture of mood disorders that affect cognitive, psychomotor and psychosocial performance accompanied by difficulties in interpersonal relationships. Methods: The research strategy employed in this study was a cross-sectional descriptive analytical survey. Total sampling with a sample size of 47 individuals was used in the sample procedure. In order to gather this information, questionnaires were distributed. Chi-Square test for data analysis. Results: This research found that bullying behaviors were associated with depressive symptoms. Of those who participated, it is known that 48.1% were bullied whereas 51.1% were not. In the normal-mild group, 46.8% exhibited depressive symptoms, in the moderate group, 29.8%; and in the severe-very severe group, 23.4%. A p-value of 0.010 was produced by the statistical test known as the Chi-Square Test. Conclusion: There was a significant correlation between Bullying Behavior and Depressive Symptoms among Vocational High School in batam. Keywords: Bullying Behavior, Depression Symptoms, Adolescents